Representasi karakter tokoh Jati Wesi dalam Novel Aroma Karsa Karya Dee Lestari dan pemanfaatannya sebagai pembelajaran Bahasa Indonesia - Hamidah, Rifa Dwi; Sabardila, Atiqa (Aksara: Jurnal Bahasa dan Sastra, 2023)
The character of Jati Wesi in theinovel Aroma Karsa has a character thattcanbbeeuseddas a good roleemodel forrreaders, including theeyounger generation. The representation of the character of Jati Wesi contains several values of character education. The purpose of this article isstoodescribe (1) theeintrinsic elements offthe Aroma Karsa novel, (2) the character educationivalues represented by the character Jati Wesi in Dee Lestari's Aroma Karsa novel, and (3) the utilization of the representation of the value of Jati Wesi character education in learning Indonesian. The research methodiused is a qualitative descriptive method. The source of data in this study is the novel Aroma Karsa by Dee Lestari in the form of text and quotes in the novel document. The results of the research found are (a) there are intrinsic elements of Dee Lestari's Aroma Karsa novel including themes, plot, characterizations, setting, point of view, and mandate, (b) there are four values of character education that represent the character of Jati Wesi. Theivalues of character education are hard work, creative, independent, and curiosity, and (c) the representation of the values of characterieducation can be used for learning Indonesian.Keywords: representation, character education, Indonesian language